Experimental and numerical studies on galloping of the flat-topped main cables for the long span suspension bridge during construction. Issue 163 (April 2017) - Li, Shengli; An, Yonghui; Wang, Chaoqun; Wang, Dongwei
Abstract: The flat-topped main cables of the long span suspension bridge may occur galloping in the wind field during construction; however, little about galloping of the flat-topped main cables has been found in the existing literature; so it is important to address this problem. The present paper has two main parts, i.e. the numerical simulation and the wind tunnel test. In the first part, numerical simulation using the method of CFD (Computational Fluid Dynamics) is implemented to obtain the aerodynamic coefficients of six main cables with different cross sections at different wind attack angles from −5 to 5°. Then the corresponding Den Hartog coefficients of the six cables against the angle of attack are determined to predict the transverse galloping. Moreover, the Den Hartog coefficients of the six cables are compared with each other, and results show that generally the number of wind attack angles corresponded to negative Den Hartog coefficients presents a trend of increase with the progress of the construction. In the second part, models of three representative main cables are made by rigid plastics using the Three Dimension Printing Technology, and the aerodynamic coefficients of these cables are obtained by wind tunnel test; then the aerodynamic coefficients based on numerical simulation and wind tunnel test are compared together. It can be seen that the experimental results of the relationship of aerodynamic coefficients and the wind attack angles is close to the corresponding numerical results. As a result, the numerical simulation method in this paper can be used to study the galloping of main cables with different cross sections; moreover, the probability of the galloping occurrence increases with the progress of the construction. The present work lays a good foundation for safety alerts of the flat-topped main cables in construction. Highlights: There has very little research about the Galloping of flat-topped main cables. Galloping will not happen at the early construction stage of flat-topped main cables. Galloping is more likely to happen with the construction progress of flat-topped main cables. A verified numerical method for the galloping of flat-topped main cables in construction.